P5P2RA TINGKATKAN KESADARAN BERBANGSA DAN BERNEGARA MELALUI TEMA KEARIFAN LOKAL SERTA KEWARGANEGARAAN DAN KEBANGSAAN - Agusta, Erna Sari (LPMP Provinsi DKI Jakarta, 2023)
The lack of students' knowledge about ethnic, cultural and religious diversity causes low awareness of the nation and state. Based on the results of the preliminary study it is known that less than 50% of students know ethnicity, culture and religion in Indonesia, 50% of students are not responsive to the presence of followers of other religions in their neighborhood, only 2 out of 8 students give a positive view of religious diversity in Indonesia , and frequent cases related to chauvinism and disciplinary violations. Learning innovations are needed through P5P2RA with the themes of Local Wisdom and Citizenship and Nationality which can make students involved and learn independently. This study aims to foster awareness of nation and state among students. This type of research is qualitative with a descriptive method. This research was conducted at MTsN 28 Jakarta for 7 weeks from 5 May – 2 June 2023. The research subjects were 7th grade students, totaling 192 students. Data was collected through observation, interviews, documentation and questionnaires. Data analysis was carried out on the four indicators of national and state awareness. The results showed that the acquisition of the results of the questionnaire on each indicator of national and state awareness reached more than 75% in each class. Likewise, case data related to chauvinism and disciplinary violations has decreased by up to 50% within 3 months after the implementation of P5P2RA. Thus it can be said that P5P2RA with the theme of Local Wisdom and Citizenship and Nationality can foster awareness of the nation and state in MTsN 28 Jakarta students.